Battling with Lanchester's equations in the classroom. Issue 3 (16th March 2023) - McCartney, M.
Abstract : A discrete time version of Lanchester's 'aimed fire' model for combat is considered. The resulting equations are treated as a model for repeated battles and the effect of rearmament between battles is investigated. The usefulness of considering the solution of the model in the phase-plane is emphasized and a number of possible classroom extension exercises are included.